Effects of Contact Characteristics on Dynamic Response of Planar Mechanical Systems with Lubricated Revolute Joint - Xu Peng; Haoran Zhu; Yang Guo; Xuze Wu; Yu Chen (Lubricants)
In this study, a dynamic response model that incorporates lubricated clearance is developed to examine the evolution of contact and friction in a mechanical system. The dynamic model of a lubricated clearance joint is established by considering the contact, friction, and hydrodynamics. The expression of contact force in normal and tangential directions is developed using elastic contact theory. The lubrication characteristics of a revolute joint are obtained using hydrodynamic theory, which is introduced into the simulation model. This case study is conducted to investigate the effects of design parameters on the dynamic stability of a mechanical system with a lubricated clearance joint. The results elucidate the relationship between lubrication characteristics and vibration response, offering valuable insights for the optimization of mechanical systems.